2019
DOI: 10.3390/catal9030269
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Electrochemical Performance of Zn-Doped La0.2Sr0.25Ca0.45TiO3 Infiltrated with Nickel-CGO, Iron, and Cobalt as an Alternative Anode Material for Solid Oxide Fuel Cells

Abstract: In solid oxide fuel cells, doped strontium titinates have been widely studied as anode materials due to their high n-type conductivity. They are used as current conducting backbones as an alternative to nickel-cermets, which suffer degradation due to coking, sulphur poisoning, and low tolerance to redox cycling. In this work, anode backbone materials were synthesized from La0.2Sr0.25Ca0.45TiO3−δ (LSCTA-), modified with 5 wt.% Zn, and infiltrated with nickel (Ni)/ceria gadolinium-doped cerium oxide (CGO), Fe, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, the electrochemical performance of SrTiO 3 -based anodes is very low without additional catalyst infiltration, as reported by e.g. N. Muzaffar et al [16] who observed a decrease in polarization resistance at 750 • C and 3% H 2 O/H 2 from 25 Ω cm 2 to below 0.1 Ω cm 2 when Ni:CGO was infiltrated.…”
Section: Introductionmentioning
confidence: 74%
“…However, the electrochemical performance of SrTiO 3 -based anodes is very low without additional catalyst infiltration, as reported by e.g. N. Muzaffar et al [16] who observed a decrease in polarization resistance at 750 • C and 3% H 2 O/H 2 from 25 Ω cm 2 to below 0.1 Ω cm 2 when Ni:CGO was infiltrated.…”
Section: Introductionmentioning
confidence: 74%
“…In addition, in some studies a metal catalyst is added, in order to enhance the reactivity for fuel oxidation. 8,40,[46][47][48][49][50] As an alternative structural architecture, perovskite-CGO composite backbones are fabricated, with or without additional metal catalyst infiltration. This type is also reported as a promising SOFC anode.…”
Section: Composite Conductivity In Porous Miec Soc Composite Electrodesmentioning
confidence: 99%
“…In order to improve the electrocatalytic activity of these materials, dopants are introduced in B-sites (Ni, Co, Fe, Mn etc.) (22)(23)(24)(25)(26). In addition, LSCTA-possess an oxygen chemical diffusion coefficient of 3.406 × 10 −7 cm 2 s −1 , within one order of magnitude of the oxide-ion conductor 8YSZ, providing the material with impressive ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%